Soil carbon dynamics and enzymatic activities under different resource conservation technologies in rice- green gram cropping system - Dash, P K; Bhattacharyya, P; Shahid, Md.; Nayak, A K (ORYZA-An International Journal of Rice, 2018)
The effects of different resource conservation practiceson SOC pools, soil enzymatic activities were studiedÂ under tropical lowland rice (Oryza sativa L.)- green gram (Vigna radiata) soilsystem in a long-termÂ experiment,which was established in 2012. Seven RCTs i.e., conventional farmer’s practice, brown manuring,Â green manuring, wet direct drum seeding, zero tillage, green manuring plus real time nitrogen management byÂ customized leaf colour chart and biochar application were broadly included in the experiment.Soil organic carbon (SOC) pools were significantly higher under Green manuring treatment compared to conventionalÂ control. Soil labile carbon fractions and enzymatic activities were significantly higher under RCTs over control.Â Soil organic carbon was significantly higher under zero tillage as compared to other resource conservationÂ practices as well as conventional treatments and 13% more than that of conventional control. It can be concludedÂ from the experimental data that resource conservation practices like zero tillage could offer carbon saving byÂ increase soil carbon stock in tropical lowland rice-green gram soil.